Strategi masyarakat pesisir Margolinduk dalam penanganan banjir rob serta implikasi terhadap sikap peduli lingkungan - Bariroh, Ghurrotul; Surtikanti, Hertien Koosbandiah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Margolinduk Village is one of the coastal villages on the north coast of Central Java which is worst affected by the tidal floods in Demak Regency. The various losses felt by the people of Margolinduk Village due to tidal floods have not reduced the resilience of the people to stay put. So that various handling efforts are deployed by the community in order to survive. However, so far there has been no research that examines the strategies of the Margolinduk Village community in dealing with tidal floods. Therefore, this research aims to find out the strategies used by the Margolinduk Village community in dealing with tidal floods and the implications for attitudes toward caring for the environment. Community efforts to deal with tidal floods should lead to concern for the environment. However, this attitude of caring for the environment must be proven by measuring indicators of caring for the environment. The method in this research is descriptive qualitative. Data collection was carried out through questionnaires, interviews, and observations. The number of samples used in this research was 30 people taken by purposive sampling. The Margolinduk Village community's strategy for dealing with tidal floods is by raising house buildings and looking for other alternative jobs. Even though the education level of the people of Margolinduk Village is still relatively low, the attitude of caring for the environment of the people of Margolinduk Village is in the very good category. Thus, what is found in this research is that attitudes that care about the environment do not always arise because of the knowledge taught at school. Direct experiences or individual impacts due to tidal floods have deep emotional and practical dimensions, thus playing a crucial role in shaping changes in attitudes and behavior towards greater environmental awareness.